An Attractiveness of Sarawak as Ecotourism Destination: An overview of Natural Based Market Segment - Lee, Goi Chai; Leh, Chieng Fayrene Yew (Indian Journal of Marketing, 2008)
Number of researchers elaborated ecotourism into few major principles: interest in nature; education and study; enjoyment and appreciation; culture; contributes to conservation; benefits local people; non-consumptive; and sustainable. There is a growing consensus that ecotourism consists of three basic criteria: natural and cultural attractions, educational or learning experiences and environmental, economic and socio-cultural sustainability (Blamey 1997, Weaver 2001). Thus, the main objective of this study is to review the ecotourism in Sarawak, mainly based on three factors of nature-based market segment: natural and cultural attractions; educational and learning experiences; and environment, economic and socio-cultural sustainability.